A biopsychosocial model of MDMA-assisted therapy in application: Dyadic One Session Treatment for specific phobia - Ahari, Nicholas J.; Fonzo, Gregory A. (Frontiers in Psychiatry, 2025)
3,4-methelenedioxymethamphetamine (MDMA) can be effective in treating posttraumatic stress disorder (PTSD) in controlled trials, potentially secondary to MDMA’s effects on neural circuits implicated in fear and reward. Although anxiety, stress, and fear-based disorders involve maladaptation of the neural circuits processing fear, threat, and reward, no studies have tested MDMA’s therapeutic efficacy on specific phobias. This article proposes a naturalistic biopsychosocial model of MDMA assisted therapy (MDMA-AT) informed by the neurobiological mechanisms of MDMA and the theoretical models of Emotional Processing Theory (EPT), inhibitory learning, and cognitive behavioral interpersonal theory (CBIT) to inform transdiagnostic treatments for anxiety, stress, and fear-based disorders. As a fear-based disorder with a circumscribed focus, we apply the biopsychosocial model to propose a novel MDMA-assisted Dyadic One Session Treatment (DOST) model for spider phobia, one of the most common animal phobias. Specific phobias such as spider phobia offer a straightforward naturalistic model to test the effects of MDMA on normalizing approach behavior, avoidance behavior, and neural circuit function. We hypothesize that the neurobiological and prosocial effects of MDMA can promote enhanced emotional processing and inhibitory learning of phobic stimuli during exposure exercises to create more adaptive associations that lead to increases in approach behavior and reductions in spider phobia symptomatology. Such a model may spur greater thought towards integration of evidence-based exposure therapies (ETs) designed to optimally capitalize upon the pharmacological effects of MDMA and other psychedelic compounds to treat fear-based mental health conditions.